2020
DOI: 10.3389/fonc.2020.01198
|View full text |Cite
|
Sign up to set email alerts
|

Immune Landscape of the Tumor Microenvironment Identifies Prognostic Gene Signature CD4/CD68/CSF1R in Osteosarcoma

Abstract: Background: Osteosarcoma (OSA), the most common primary bone malignancy in children and adolescents, is prone to metastases and unfavorable prognosis. Owing to its strong genomic heterogeneity, traditional chemotherapy, or targeted immunotherapy has not effectively improved the related overall survival for decades. Since the landscape of the OSA tumor immune microenvironment is scarcely known, despite it playing a crucial role in predicting clinical outcomes and therapeutic efficacies, we aimed to elucidate it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 51 publications
4
26
0
Order By: Relevance
“…As not all OS patients have greater benefit from immunotherapy, more immune microenvironment characteristics should be incorporated to instruct clinical treatment. Researchers have made great effort to reveal the role of tumor microenvironment and tumor microenvironment-related genes in OS by a series of bioinformatics methods [ 12 14 , 23 , 24 ]. In the present study, the ConsensusClusterPlus algorithm was utilized to identify the five reproducible immune subtypes in 87 OS patients from the TARGET database.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As not all OS patients have greater benefit from immunotherapy, more immune microenvironment characteristics should be incorporated to instruct clinical treatment. Researchers have made great effort to reveal the role of tumor microenvironment and tumor microenvironment-related genes in OS by a series of bioinformatics methods [ 12 14 , 23 , 24 ]. In the present study, the ConsensusClusterPlus algorithm was utilized to identify the five reproducible immune subtypes in 87 OS patients from the TARGET database.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al first established the prognostic signature based on immune microenvironment-related genes for OS [ 14 ], and Hu et al performed comprehensive analysis of prognostic tumor microenvironment-related genes based on several validated genes [ 23 ]. Song et al identified a set of immune gene signature related to clinical response and was verified based on 45 OSA primary tumors [ 12 ]. Our work differs from these studies in several important aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another set of studies find genes with prognostic values by applying Cox model on survival data or performing differentially expressed genes analysis between two groups of interest, and then investigate the relationship between these genes and estimated immune infiltrates [ 26 30 ]. Others study the association of immune abundance with clinical information directly [ 24 , 31 34 ]. Our work falls somewhat into the third category.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the degree of cell-killing T cell in ltration is very low, with only (1.8 cells/HPF) [29]. Devalaraja et al con rmed that sarcoma cells can release RA and promote the differentiation of monocytes in the tumor microenvironment into tumor-associated macrophages in animal models, thereby inhibiting the in ltration of antitumor T-cells [30] and also weakening the clinical effect of immune-checkpoint blockade [31]. This nding was highly recommended by Balkwill for its potential implementation on immunotherapy of sarcomas [32].…”
Section: Introductionmentioning
confidence: 99%